Vascular Regulation by Super Enhancer-Derived LINC00607 - Sriram, Kiran; Luo, Yingjun; Yuan, Dongqiang; Malhi, Naseeb Kaur; Tapia, Alonso; Samara, Vishnu Amaram; Natarajan, Rama; Bouman Chen, Zhen (Frontiers in Cardiovascular Medicine, 2022)
Vascular endothelial cells (ECs) play a pivotal role in whole body homeostasis. Recent advances have revealed enhancer-associated long non-coding RNAs (lncRNAs) as essential regulators in EC function. We investigated LINC00607, a super enhancer-derived lncRNA (SE-lncRNA) in human arteries with an emphasis on ECs. Based on public databases and our single cell RNA-sequencing (scRNA-seq) data from human arteries collected from healthy and diabetic donors, we found that LINC00607 is abundantly expressed in the arteries and its level is increased in diabetic humans. Using RNA-sequencing, we characterized the transcriptomes regulated by LINC00607 in ECs and vascular smooth muscle cells (VSMCs) and in basal and diabetic conditions in ECs. Furthermore, through transcriptomic and promoter analysis, we identified c-Myc as an upstream transcription factor of LINC00607. Finally, using scRNA-seq, we demonstrated that modified antisense oligonucleotide inhibitor of LINC00607 can reverse dysfunctional changes induced by high glucose and TNFα in ECs. Collectively, our study demonstrates a multi-pronged approach to characterize LINC00607 in vascular cells and its gene regulatory networks in ECs and VSMCs. Our findings provide new insights into the regulation and function of SE-derived lncRNAs in both vascular homeostasis and dysfunction in a cell-type and context-dependent manner, which could have a significant impact on our understanding of epigenetic regulation implicated in cardiovascular health and diseases like diabetes.